The ovarian reserve as target of insulin/IGF and ROS in metabolic disorder-dependent ovarian dysfunctions. Issue 3 (16th September 2021) - Dri, Maria; Klinger, Francesca Gioia; De Felici, Massimo
Abstract : It is known for a long time that metabolic disorders can cause ovarian dysfunctions and affect a woman's fertility either by direct targeting follicular cells and/or the oocytes or by indirect interference with the pituitary-hypothalamic axis, resulting in dysfunctional oogenesis. Such disorders may also influence the efficiency of the embryo implantation and the quality of the embryo with permanent effects on the fertility and health of the offspring. Thanks to the expanding knowledge on the molecular mechanisms governing oogenesis and folliculogenesis in mammals, we are beginning to understand how such disorders can negatively affect this process and consequently fertility in women. In the present review, we point out and discuss how the disturbance of insulin/IGF-dependent signalling and increased reactive oxygen species (ROS) level in the ovary typically associated to metabolic disorders such as type II diabetes and obesity can dysregulate the dynamics of the ovarian reserve and/or impair the survival and competence of the oocytes. Lay summary: In women, a progressive decline and depletion of the primary ovary reserve, which represents the reserve of immature eggs, are a challenging condition in the field of reproductive medicine. This decline, occurring physiological with age, is the main determinant of the age at the onset of menopause. Concomitant with the reduction in their number, the quality of the eggs also decreases with age. Metabolic disorders such as diabetes and obesity can cause ovarian dysfunctions and affect a woman's fertility mainly by direct targeting the egg stockpile or by indirect interference with the production of reproductive hormones. Here, we report up-to-date data and discuss results about how disturbance of insulin-dependent signalling and increased oxidative stress in the ovary, usually associated to metabolic disorders, can dysregulate the dynamics of the primary ovary reserve and/or impair the survival and quality of the eggs.